Omalizumab restores the ability of human plasmacytoid dendritic cells to induce Foxp3+Tregs. Issue 1 (14th January 2021) - López-Abente, Jacobo; Benito-Villalvilla, Cristina; Jaumont, Xavier; Pfister, Pascal; Tassinari, Paolo; Palomares, Oscar
Allergic sensitisation and viral respiratory tract infections represent the main risk factors for asthma development and severity. IgE plays a key role in the pathophysiology of allergic asthma and allergic multimorbidities [1, 2]. Omalizumab, a recombinant humanised monoclonal antibody against IgE, has been used to treat allergic asthma in children and adults for many years [3–5]. Omalizumab restores the capacity of human plasmacytoid dendritic cells (pDCs) to produce interferon (IFN)-α, increasing their antiviral activity and reducing viral-induced asthma exacerbations [6, 7]. pDCs prime T-helper cell (Th)1 or Th2 responses depending on the encountered antigens. IgE-FcεR1 cross-linking on human pDCs impairs their capacity to generate regulatory T-cells and in vitro omalizumab restores this ability. These findings may pave the way for novel biomarkers to assess omalizumab clinical efficacy and responder patients. https://bit.ly/2ZQbJ9t